Comparative Analysis of Cash Holding Based on Leverage, Capital Expenditure and Firm Size Factors of Companies in the Properties and Real Estate Sector on the Indonesia Stock Exchange - Rompas, Jarden Natanael; Gamaliel, Hendrik; Lambey, Robert (Formosa Journal of Multidisciplinary Research, 2024)
The availability of cash in a company is very important because, without sufficient cash, the company's operational activities cannot run optimally. This research aims to empirically test the comparison of cash holdings based on leverage, capital expenditure and firm size of companies in the properties and real estate sector on the Indonesia Stock Exchange for the 2020-2022 period. Cash holding is measured by the ratio of cash and cash equivalents to total assets, leverage is measured by DER, capital expenditure is measured by the comparison between the difference between fixed assets from the current year and the previous year and total assets, firm size is measured by the natural logarithm of total sales. This type of research is quantitative comparative test research using secondary data. The sampling technique used was non-probability sampling with a purposive sampling method and resulted in 58 company samples from 69 companies. The data analysis technique used in this research is the Mann Whitney test using SPSS 27 for Windows software. The research results show that there are differences in cash holding based on capital expenditure and firm size. Meanwhile, there is no difference in cash holding based on leverage.